An analysis of the role of rural development initiatives in promoting sustainable and effective development in the Eastern Cape : a case study of Intsika Yethu Municipality - Sango, Nolubabalo (Stellenbosch : Stellenbosch University, 2022)
Thesis (MPA)--Stellenbosch University, 2022.